Redefining Shareholder Value Maximization: Identifying key sustainable investment strategies and their role in rehabilitating corporate purpose - Duong, Iris Wan Wan (Consilience, 2022)
The purpose of this essay is to situate investing in a commercial context where consideration of ESG and impact factors at the least does not compromise investment returns, and hence excludes discussions on non-profits, private foundations and charitable organizations. Instead, I look into pension funds, private equities and hedge funds whose primary fiduciary duty is to serve the economic interest of beneficiaries. Grounded in case studies and real-life interviews, this essay explore ways in which investors can transcend their roles of merely financiers to become gatekeepers, value creators and reformers of corporate mission, steering companies towards the path of sustainability. Ultimately, by examining the regulatory framework, valuation models and implementation tactics of various sustainable investment strategies, this essay seeks to illuminate a new understanding of ‘value maximization’ that ties positive externalities to long-term portfolio performance.